2007
DOI: 10.1111/j.1365-2958.2007.06064.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium common nod genes are required for biofilm formation

Abstract: SummaryIn legume nitrogen-fixing symbioses, rhizobial nod genes are obligatory for initiating infection thread formation and root nodule development. Here we show that the common nod genes, nodD1ABC, whose products synthesize core Nod factor, a chitin-like oligomer, are also required for the establishment of the three-dimensional architecture of the biofilm of Sinorhizobium meliloti. Common nod gene mutants form a biofilm that is a monolayer. Moreover, adding Nod Factor antibody to S. meliloti cells inhibits b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 42 publications
3
50
1
5
Order By: Relevance
“…Recently, studies have shown that the production of LMW EPS II results in biofilm formation and attachment at levels as high as 10-fold greater than those produced by strains of S. meliloti incapable of synthesizing this exopolysaccharide (18,46). Thus, the ability of the bacteria to establish levels of biofilm comparable to wild-type levels was utilized as a secondary indicator of the presence or absence of the low-molecular-weight form.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have shown that the production of LMW EPS II results in biofilm formation and attachment at levels as high as 10-fold greater than those produced by strains of S. meliloti incapable of synthesizing this exopolysaccharide (18,46). Thus, the ability of the bacteria to establish levels of biofilm comparable to wild-type levels was utilized as a secondary indicator of the presence or absence of the low-molecular-weight form.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, AHL supplementation of rhizobial inoculants did not stimulate strain competitiveness and only slightly increased plant host nodulation. Nevertheless, taking into consideration that (i) numerous traits are controlled by quorum sensing regulation [28,29], (ii) the expression of rhizobial nod genes may be influenced by the metabolic status of the cells [57], and (iii) nod genes as well as quorum sensing signaling may be involved in biofilm formation [58], a connection between the presence of AHL and Nod factor synthesis cannot be excluded. If that were the case, the effect of AHL supplementation of rhizobial inoculants would be similar but weaker than the flavonoid induction and would affect plant growth (but no rhizobial competitiveness) via Nod factor synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…CM 98 roots in saline soil (Qurashi & Sabri 2012). Symbiotic genes are important for biofilm-forming rhizobia (Fujishige et al 2008). It seems that biofilm formation is positively connected with the microbe-plant symbiosis.…”
Section: Discussionmentioning
confidence: 99%